To find the 10th term of the sequence given by the formula \( a_n = n - 6 \), we need to substitute \( n = 10 \) into the formula.
\[ a_{10} = 10 - 6 \]
Calculating this gives:
\[ a_{10} = 4 \]
Therefore, the 10th term of the sequence is 4.
an = n − 6
1 answer
To find the 10th term of the sequence given by the formula \( a_n = n - 6 \), we need to substitute \( n = 10 \) into the formula.
\[ a_{10} = 10 - 6 \]
Calculating this gives:
\[ a_{10} = 4 \]
Therefore, the 10th term of the sequence is 4.